Stavovi građana Srbije o medijskoj vidljivosti socijalnih usluga namenjenih osobama sa smetnjama u razvoju - Vidojević, Marina (Specijalna edukacija i rehabilitacija, 2025)
Introduction. The introduction discusses the issue of public perception of people with developmental disabilities and the connection of media visibility of social protection services with issues of social justice and social protection as a mechanism for establishing social justice and quality of life. Objective. The research objective, part of which we present in the paper, was to discover the relationship between media transparency of social protection services and the quality of life of service users. Method. The conducted research consists of two components. In the first part, we examined the media image of social protection services in Serbia by analyzing media content, while in the second component, we used surveys to examine citizens’ attitudes about the media visibility of social protection services for people with developmental disabilities. A total of 500 participants participated in the research, including 257 service users and 243 members of the general population selected by random sampling. Results. The presentation of results with discussion is focused on the data on media visibility of social services in Serbia for the period February – July 2018, and those results show that there is a need for more balanced and comprehensive media coverage of this topic. On the other hand, there is a presentation of the data obtained through the survey with a focus on the participants’ familiarity with the social services offered in Serbia and their views on the representation of this topic in the media and the importance of that representation. Conclusion. The results lead to the conclusion that the more visible social protection services are, the more effective their implementation is; that is, media visibility of social services for people with developmental disabilities contributes to raising the quality of life of people with disabilities. The findings underline the importance of media visibility in improving the rights and well-being of persons with developmental disabilities in Serbia.
Keywords: social services; media visibility; people with developmental disabilities; quality of life